Pengaruh Rasio Prekursor Agregat Halus Terhadap Karakteristik Mortar Geopolimer Tanah Liat - R. Wijaya; E. Edowinsyah (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2023)
The basis and main component of any building construction is primarily concrete. With the rapid growth of global construction, the demand for concrete is increasing and consequently the demand for cement as the main component in making concrete is also increasing. This is the single most important factor for using inorganic binders to obtain eco-friendly concrete. Nowadays, inorganic binders such as geopolymers or alumina-silicate polymers are used in many advances of eco-friendly concrete. Geopolymer mortar is one that uses natural components and minerals as binders and has a high concentration of alumina and silica oxide. This study aims to determine how the ratio of precursor (clay) fine aggregate affects the characteristics of geopolymer mortar. The research method used is the Experimental method, alkaline activator with a ratio of 1:1 in NaOH and Na2SiO3 and using 16 M molarity NaOH. Using precursor and fine aggregate in the ratio of 1:0.2; 1:0.4; 1:0.6; 1:0.8; 1:1; 1:1.2; 1:1.4; 1:1.6; 1:1.8 and 1:2. At the age of 3, 14, and 28 days, compressive strength tests were conducted on all specimens. Based on the results of the research, the compressive strength of clay geopolymer mortar has a maximum compressive strength of 8.53 MPa after 28 days of treatment with code M6 at a precursor and fine aggregate ratio of 1: 1.2. The results showed that after passing the maximum compressive strength ratio in code M6 the ratio decreased due to more fine aggregate than the binder (alkali activator).